UNIT 2.23 FRET Imaging by Laser Scanning Cytometry on Large Populations of Adherent Cells. Issue 1 (1st October 2014) - Doan‐Xuan, Quang‐Minh; Szalóki, Nikoletta; Tóth, Katalin; Szöllősi, János; Bacso, Zsolt; Vámosi, György
Abstract: The application of FRET (fluorescence resonance energy transfer) sensors for monitoring protein‐protein interactions under vital conditions is attracting increasing attention in molecular and cell biology. Laser‐scanning cytometry (LSC), a slide‐based sister procedure to flow cytometry, provides an opportunity to analyze large populations of adherent cells or 2‐D solid tissues in their undisturbed physiological settings. Here we provide an LSC‐based three‐laser protocol for high‐throughput ratiometric FRET measurements utilizing cyan and yellow fluorescent proteins as a FRET pair. Membrane labeling with Cy5 dye is used for cell identification and contouring. Pixel‐by‐pixel and single‐cell FRET efficiencies are calculated to estimate the extent of the molecular interactions and their distribution in the cell populations examined. We also present a non‐high‐throughput donor photobleaching FRET application, for obtaining the required instrument parameters for ratiometric FRET. In the biological model presented, HeLa cells are transfected with the ECFP‐ or EYFP‐tagged Fos and Jun nuclear proteins, which heterodimerize to form active AP1 transcription factor. Curr. Protoc. Cytom . 70:2.23.1‐2.23.29. © 2014 by John Wiley & Sons, Inc.